Phonological Variation and Social Stratification: Evidence from Urban Speech Communities - Shaumiwaty Shaumiwaty; Nino Tsereteli; Aminata Ceesay (Journal of Humanities Research Sustainability, 2026)
Background. Phonological variation is a crucial aspect of sociolinguistics, reflecting social hierarchies, identities, and group affiliations within speech communities. Urban areas, characterized by diverse populations and socio-economic stratification, provide an ideal context for studying how phonological features correlate with social class, ethnicity, and other social variables. Understanding the relationship between phonological variation and social stratification offers valuable insights into the complex dynamics of language use in multicultural and urban settings. Purpose. This study aims to explore how phonological variation manifests in urban speech communities and its connection to social stratification. By examining specific phonological features and their distribution across different social groups, the research seeks to uncover patterns of linguistic differentiation and their relationship to social factors such as class, education, and ethnicity. Method. A mixed-methods approach is employed, combining quantitative acoustic analysis of speech samples with qualitative interviews from a range of socio-economic groups in an urban area. Data was collected from spontaneous conversations, interviews, and public speeches to ensure a broad representation of speech patterns. Results. The study reveals significant phonological variation across social strata, with certain phonetic features strongly correlating with higher social status and education levels. Variations in vowel and consonant pronunciation were notably influenced by social class and ethnic background. Conclusion. This research highlights the role of phonological variation in signaling social identity and reinforces the connection between language and social stratification in urban settings.